If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (11r + 9)(2r + -3) = 0 Reorder the terms: (9 + 11r)(2r + -3) = 0 Reorder the terms: (9 + 11r)(-3 + 2r) = 0 Multiply (9 + 11r) * (-3 + 2r) (9(-3 + 2r) + 11r * (-3 + 2r)) = 0 ((-3 * 9 + 2r * 9) + 11r * (-3 + 2r)) = 0 ((-27 + 18r) + 11r * (-3 + 2r)) = 0 (-27 + 18r + (-3 * 11r + 2r * 11r)) = 0 (-27 + 18r + (-33r + 22r2)) = 0 Combine like terms: 18r + -33r = -15r (-27 + -15r + 22r2) = 0 Solving -27 + -15r + 22r2 = 0 Solving for variable 'r'. Factor a trinomial. (-9 + -11r)(3 + -2r) = 0Subproblem 1
Set the factor '(-9 + -11r)' equal to zero and attempt to solve: Simplifying -9 + -11r = 0 Solving -9 + -11r = 0 Move all terms containing r to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -11r = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -11r = 0 + 9 -11r = 0 + 9 Combine like terms: 0 + 9 = 9 -11r = 9 Divide each side by '-11'. r = -0.8181818182 Simplifying r = -0.8181818182Subproblem 2
Set the factor '(3 + -2r)' equal to zero and attempt to solve: Simplifying 3 + -2r = 0 Solving 3 + -2r = 0 Move all terms containing r to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2r = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2r = 0 + -3 -2r = 0 + -3 Combine like terms: 0 + -3 = -3 -2r = -3 Divide each side by '-2'. r = 1.5 Simplifying r = 1.5Solution
r = {-0.8181818182, 1.5}
| 87/111 | | (-4-2y)+3y=-1 | | 25*ln(x)+19*ln(x)+13*ln(x)= | | 2x-9x+4x=7 | | x-3=2+3y | | ln(x+5)=0.2 | | (X+4)+(2x-3)= | | 0.2=ln(x+5) | | (X+4)+(2x+3)= | | x^3+6x+8=0 | | 7+5x=-13+7x | | -w-4/2=0 | | 3(x-7)+3x=-3 | | (4-2y)+3y=-1 | | 2(x-6)-3x=-2 | | -56x+45z^2-45=0 | | 5(t-4)+5t=5(2t+4)-11 | | 6(k-7)=9(k) | | 0.4(x+50)+0.8=56 | | A=1/3zks | | 4+6n-3=4n+17-2n | | 6x^2=54x+36-0 | | 7l^2-274l-440=0 | | 7=20-16x^2 | | 37/6= | | F(x)=3x^2+5x-6 | | 18(t-3)+3t=7(3t+3)-10 | | V-b=5 | | 0.30x+0.05(12-x)=0.10(21) | | 0.5x-1.1=3.6x+2.3 | | 72y=180 | | y+72y=180 |